The radio theater as a humanistic experience in the teaching and learning processes in remote face-to-face model - Barquero Alfaro, Julio (2022)
Due to the consequences of the Pandemic, the Centre for General Studies has modified its face-to-face academic activities migrating towards a remote attendance mode, betting on digital alphabetization with a deep commitment to excellence in an uncertain context, which represented a spectrum of educational opportunities supported by technological resources. Creative and scenic games used during the teaching experience, facilitated a sort of practical lab for ne expressive languages from a humanist standpoint in which actual practice, collective interactions, playful relations, are the essential pillars for the new learning processes. The new methodological approach generated processes of research and training that encompass significant possibilities for adaptability and creative skills thanks to the use of the technique known as Radio-theater, which consists in developing performance skills and digital capacities to produce quality scenic material and critical content using theatrical and technological resources.